2008
DOI: 10.1002/cjce.20027
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition of carbon steel under two‐phase flow (water‐petroleum) simulated by turbulently agitated system

Abstract: The corrosion of carbon steel in single-phase (water with 0.1N NaCl) and two immiscible phases (kerosene-water) using turbulently agitated system was investigated. The experiments were carried out for Reynolds number (Re) range of 38 000 to 95 000 using circular disc turbine agitator at 40 • C. In two-phase system, test runs were carried out in aqueous phase (water) concentrations of 1% vol, 5% vol, 8% vol, and 16.4% vol mixed with kerosene at various Re. The effect of Re, percent of dispersed phase, dispersed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This has been evidenced by previous works (Schmitt and Rothman, 1995; Nesic et al, 1995;George and Nesic, 2007;Aziz, 2014) that have reported a weak flow dependence of corrosion rate or even a decrease in the corrosion rate with increased flow. Secondly, when the agitation velocity increases, the dispersion of CO 2 gas in the liquid will be increased by increasing the number of bubbles due to high shear force that cause a breakage of large bubbles into small bubbles (McCabe et al, 2001;Zacconeb et al, 2007;Slaiman et al, 2008) which in turn increase the number of bubbles striking the metals. Because CO 2 gas is not as corrosive as dissolved CO 2 , the corrosion rate and I g decrease.…”
Section: Effect Of Agitation Velocitymentioning
confidence: 98%
“…This has been evidenced by previous works (Schmitt and Rothman, 1995; Nesic et al, 1995;George and Nesic, 2007;Aziz, 2014) that have reported a weak flow dependence of corrosion rate or even a decrease in the corrosion rate with increased flow. Secondly, when the agitation velocity increases, the dispersion of CO 2 gas in the liquid will be increased by increasing the number of bubbles due to high shear force that cause a breakage of large bubbles into small bubbles (McCabe et al, 2001;Zacconeb et al, 2007;Slaiman et al, 2008) which in turn increase the number of bubbles striking the metals. Because CO 2 gas is not as corrosive as dissolved CO 2 , the corrosion rate and I g decrease.…”
Section: Effect Of Agitation Velocitymentioning
confidence: 98%
“…The pressure drop across the tube in which the two phase fluid was flowing was measured using inverted U tube manometer connected to pressure taps attached to the tube wall. For experiments with oil, Reynolds number of hot fluid ( Re h ) was calculated based on the physical properties of continuous phase . When calculating the U o , the physical properties of the dispersion mixture (density, viscosity, thermal conductivity, and heat capacity) were calculated using mixing rule and taken at the bulk temperature.…”
Section: Experimental Workmentioning
confidence: 99%
“…The effect of screw was ignored. The chemical composition of specimen is shown in Table 1 Before each test run, the metal specimen was abraded with glass emery paper of grade numbers: 120, 180, 220, 400 and 2000 respectively, washed by tap water followed by distilled water, dried with a clean tissue followed by ethanol for 30 seconds, dried with clean tissue, and then dried by using electrical oven at a temperature of 110 ºC for 10 minutes [5,6,7].…”
Section: Experimental Workmentioning
confidence: 99%